A study on the knowledge, attitudes, and practices of Asian dermatologists in the management of atopic dermatitis - Siqing Ee; Yong-Kwang Tay; Chia-Yu Chu; Kam-Lun Ellis Hon; Kin-Fon Leong; Siriwan Wananukul (Wolters Kluwer Medknow Publications, 2020)
Background: Atopic dermatitis (AD) is a prevalent skin disease in Asia. Attitudes and practice vary among the Asian cities. Objectives: This study aimed to survey similarities and differences in dermatologists' attitudes and practice in Asian cities. Methods: A questionnaire survey was sent to 118 dermatologists in Singapore, Malaysia, Thailand, Taiwan, and Hong Kong. Results: About 30.8% of respondents from Taiwan and 44.4% of respondents from Hong Kong saw most of their patients presenting with severe AD. This is significantly higher than respondents from Singapore, Malaysia, and Thailand (4%-12%). Majority of the respondents would use topical corticosteroids in infants and children with AD. About 55.6% of the respondents from Hong Kong used topical calcineurin inhibitors in AD, which is a significantly lower than the other countries. Top 3 most prescribed antibiotics in infected AD were cephalexin, cloxacillin, and amoxicillin/clavulanic acid combination. Most respondents used oral corticosteroids in severe AD. Many respondents from Singapore and Malaysia use cyclosporin (70%-92%), azathioprine (80%-100%), and methotrexate (72%-75%). Fewer respondents from Thailand, Taiwan, and Hong Kong used cyclosporin (22.2%-59%), azathioprine (0%-66.7%), and methotrexate (8%-25.6%). A large majority of respondents from Singapore, Taiwan, and Malaysia use phototherapy in management of AD (90%-100%). About 24% of respondents from Thailand and 33.3% of respondents from Hong Kong use phototherapy in AD. Conclusion: Compared to the previous study, there is improvement in the proportion of dermatologists in Asia using topical calcineurin inhibitors and phototherapy. This may signify better access to these treatment modalities throughout the region. Educational programs that allow a patient-centered approach should be recommended as an adjunct to medical therapy. The management of AD among Asians requires a holistic approach while considering accessibility and cultural differences.